Loss and Damage Financing in the Climate Justice Debate - Ikporukpo, Chris O.; Ikporukpo, Ninane Nina (Advances in Social Sciences Research Journal, 2024)
The concept of Loss and Damage (L & D) emerged as a contentious issue during the negotiations for the United Nations Framework Convention on Climate Change (UNFCCC). The framing of the concept and the demand for a Loss and Damage Fund were both controversial. It is these controversial dimensions of the climate change regime that are analysed in this article. The data were obtained from mainly publications of UNFCCC Secretariat, the Intergovernmental Panel on Climate Change, climate negotiation blocs and civil society organisations. Based on a sample of thirty-six sources, the varied conceptualisations of L & D are examined. The concept was politicised. Be that as it may, it was in the demand for L & D financing that the influence of politics was particularly apparent. The demand brought into conflict the Global South and the Global North. The basic argument of the Global South in its demand for a L & D Fund was based on the need for climate justice. In spite of the fact that the demand started as early as 1991, it was only in 2022 during COP 27 in Egypt that the Global North accepted in principle, based on an understanding that liability and compensation were not involved. The Fund was formally established during COP 28 in Dubai in 2023. However, issues of effective funding remain.